Determinan Kemiskinan Provinsi Daerah Istimewa Yogyakarta: Pendekatan Data Panel Tahun 2018-2024 - Maulia Siti Mukharohmah; Nurul Fadhilah (Jurnal Riset Daerah, 2025)
This study aims to analyze the socioeconomic, health, and demographic factors influencing poverty levels in the Special Region of Yogyakarta (DIY). The variables examined include Average Years of Schooling (RLS), the Human Development Index (HDI), Life Expectancy (UHH), total population, the Open Unemployment Rate (TPT), Gross Regional Domestic Product (GRDP), and the Regency/Municipal Minimum Wage (UMK). This research employs a quantitative approach using secondary panel data from the Central Bureau of Statistics (BPS) for the five regencies/municipalities in DIY from 2018 to 2024. Data analysis was conducted using a Fixed Effect panel regression model with Stata 17. The results indicate that HDI has a negative and significant effect on poverty levels, while Life Expectancy and the Open Unemployment Rate have positive and significant effects. Meanwhile, Average Years of Schooling, total population, GRDP, and UMK do not exhibit significant effects on poverty. These findings suggest that improving human capital quality and reducing unemployment are key factors in alleviating poverty in DIY. The study provides important implications for policymaking, particularly in enhancing education quality, health services, and employment opportunities. It also highlights potential avenues for further research, including the incorporation of additional socioeconomic variables and the application of spatial approaches to analyze poverty distribution patterns across regions in DIY.